PROTECTING CULTURAL HERITAGE OBJECTS IS THE CIVIC DUTY OF EACH OF US! - S.B. Murtazova; G. Egamova (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: This article generalizes information about the state policy and legal foundations regarding the preservation of cultural heritage objects in our country, as well as the essence and significance of recent activities in this field.